An Interactive System for Concurrent Engineering Design - Tan, CheeFai; V.K., Kher; S.S., S. Ranjit (Trans Tech Publications, Switzerland, 2013)
The methods in delivering engineering design have gone through evolvement where the effectiveness of conventional methods is decreasing. However, the importance of concurrent engineering design approach has tremendously increased due to the ever competitive world today. This is the reason why engineering designers are concern about the methods of delivering design and one of the recent interests is using interactive system to deliver design. In this paper, the construction of interactive system will be discussed followed by the experimental setup. Experiments will be conducted in the form of performing few selected tasks with the interactive system and comparison will be made with the conventional design approach. Comparison will be done by collecting feedback through questionnaires from the participants who are involved in the experiments. Feedback will be analysed to identify the feasibility of interactive concurrent engineering design system.